Endothelial Progenitor Cell-Based in vitro Pre-Endothelialization of Human Cell-Derived Biomimetic Regenerative Matrices for Next-Generation Transcatheter Heart Valves Applications - Motta, Sarah E.; Zaytseva, Polina; Fioretta, Emanuela S.; Lintas, Valentina; Breymann, Christian; Hoerstrup, Simon P.; Emmert, Maximilian Y. (Frontiers in Bioengineering and Biotechnology, 2022)
Hemocompatibility of cardiovascular implants represents a major clinical challenge and, to date, optimal antithrombotic properties are lacking. Next-generation tissue-engineered heart valves (TEHVs) made from human-cell-derived tissue-engineered extracellular matrices (hTEMs) demonstrated their recellularization capacity in-vivo and may represent promising candidates to avoid antithrombotic therapy. To further enhance their hemocompatibility, we tested hTEMs pre-endothelialization potential using human-blood-derived endothelial-colony-forming cells (ECFCs) and umbilical vein cells (control), cultured under static and dynamic orbital conditions, with either FBS or hPL. ECFCs performance was assessed via scratch assay, thereby recapitulating the surface damages occurring in transcatheter valves during crimping procedures. Our study demonstrated: feasibility to form a confluent and functional endothelium on hTEMs with expression of endothelium-specific markers; ECFCs migration and confluency restoration after crimping simulations; hPL-induced formation of neo-microvessel-like structures; feasibility to pre-endothelialize hTEMs-based TEHVs and ECFCs retention on their surface after crimping. Our findings may stimulate new avenues towards next-generation pre-endothelialized implants with enhanced hemocompatibility, being beneficial for selected high-risk patients.